Digital Literacy In Early Children Through Pictured Story Books - Ratnasari, Eka Mei (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2024)
Literacy is a basic skill that children need to have. This study aims to describe the introduction of literacy using digital picture storybooks for early childhood. The problems in this study show that most parents do not supervise the use of children's gadgets. Children are given gadgets so that children look calm and do not cry. So the direction given is still very minimal, especially in the use of digital storybook media. This study uses a qualitative method with a descriptive approach. The data collection techniques and tools used were observation, interviews, and documentation. Researchers used the Miles and Huberman data analysis technique. After the data was collected, the data was simplified to obtain the necessary information. Furthermore, the data were presented and organized to draw a conclusion. The book used is a digital picture storybook entitled “Tingkah Pola si Kera” which consists of text images and audio that work together to provide a complete picture of the story. The results of the analysis show that through the use of digital storybooks can provide an interesting introduction to children's digital literacy.